(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2012)
Analyzed the structural scheme of transducers of mechanical quantities on the surface acoustic waves, we consider the scheme compensation converter mechanical values, discussed issues of improving the accuracy of measurement.